As vozes da mímica pós-colonial em Terra Papagalli - Jacimara Vieira dos Santos (Estudos de Literatura Brasileira Contemporânea)
This paper draws on the studies undertaken in the area of cultural studies, inparticular,Homi Bhabha‟s formulations, to propose an analysis of the BraziliannovelTerra Papagalli(by José Roberto Torero and Marcus Aurelius Pimenta),showing how the narrative dismounts historical reality, to explore other angles; and shifts the focus to the imaginary construction that involves revisiting theDiscoveries. Thus, contrary to expectations, revealing paradoxes such as thosewhich tend to increase civic and commemorative urges that liveantagonistically, with anti-establishment thoughts that questionthe internalconnections of these developments, articulating, through mimetic resources,other voices and their critic repetitions of contested models and references.